(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This article examines the importance of the English language in modern education. The study highlights the role of English as a global language in the development of education, science, technology, and international communication. Particular attention is paid to the significance of English in accessing modern knowledge, improving professional competence, and integrating into the global educational space. The article emphasizes that mastering English is a key factor for the academic and professional success of students in the modern world.